Quantitative intersectionality: Imperatives and opportunities for advancing social equity. (5th October 2022) - Whitebread, Geoffrey; Dolamore, Stephanie; Stern, Brendan
Abstract: Social equity is a pillar of public administration (PA), yet its actualization remains elusive. The path forward to closing persistent social equity gaps requires the utilization of quantitative intersectionality in PA. This article explores the literature related to quantitative intersectionality and the imperative for use in the scholarship and practices of PA. To exemplify this concept in practice, we present a case study examining Vocational Rehabilitation performance data reports. Findings illustrate how quantitative intersectionality provides an opportunity to unpack overlapping identities for people with disabilities whose individual characteristics include historically oppressed race/ethnicity and gender identities. Findings assert the imperative for using quantitative intersectionality to achieve social equity for all.